Vegetative description of three Aquilaria (Thymelaeaceae) saplings in Malaysia - Lee, S. Y.; Ibrahim, Faridah Hanum; Mohamed, Rozi (Universiti Putra Malaysia Press, 2013)
Plants` reproductive parts are most important for species identification. However, trees such as Aquilaria species take many years to mature and produce flowers and fruits. Inconsistent and infrequent flowering periods may cause additional hindrance to classical identification. In this study, descriptions were made based on vegetative parts such as leaf, branch and bark for saplings of three Aquilaria species found in Malaysia. It was found that A. hirta sapling can be recognized through the densely hairy twigs, young shoots and axillary buds, undersurface of leaf, margin, petiole and midrib besides the strongly raised midrib, and usually unbranched habit; A. malaccensis through the many branches and white spots along main axis, entire leaf margin, slightly hairy leaf undersurface and midrib, and glabrous petiole; Aquilaria sp.1 from the lower branches that are nearly perpendicular to the stem and wavy leaf margin. These vegetative characters can serve as a basis for the correct identification of Aquilaria saplings when growers need to confirm their planting materials.